2020
DOI: 10.1039/d0tc01436b
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazolium-functionalized NU-1000: a versatile material for carbon dioxide adsorption and cyanide luminescence sensing

Abstract: The benzothiazolium-decorated NU-1000-BzTz MOF is a versatile material for carbon dioxide storage and cyanide luminescence sensing in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
(64 reference statements)
7
24
0
Order By: Relevance
“…Plonka et al found a Qst of 32 kJ/mol for FA modulated MOF-808, well in line with our findings 67 . Very similar values were reported for perfluoroalkane functionalized NU-1000 (which contains the same Zr6 cluster as MOF-808) with Qst,0 between 20 and 34 kJ/mol while the pristine NU-1000 gave a CO2 Qst,0 of 17 kJ/mol 66,68 .…”
Section: Characterization Of Mofs and Membranessupporting
confidence: 78%
“…Plonka et al found a Qst of 32 kJ/mol for FA modulated MOF-808, well in line with our findings 67 . Very similar values were reported for perfluoroalkane functionalized NU-1000 (which contains the same Zr6 cluster as MOF-808) with Qst,0 between 20 and 34 kJ/mol while the pristine NU-1000 gave a CO2 Qst,0 of 17 kJ/mol 66,68 .…”
Section: Characterization Of Mofs and Membranessupporting
confidence: 78%
“…It is attributed to the open Cu metal sites in HKUST-1 with high CO 2 affinities, which is confirmed by a high isosteric heat of CO 2 adsorption on HKUST-1 (31 kJ/mol). For CO 2 adsorption in the low-pressure region, the core improves the affinity between MOFs and guest CO 2 , which can be achieved through pore size control, , open metal sites, Lewis basic groups, and other polar groups. While it is mentioned above that the partial pressure of CO 2 in the actual industry is smaller than 1 bar, it is crucial to improve the CO 2 capture performance of MOFs at low pressure for pursuit of industrial applications of MOFs adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The metal clusters, bridged groups, and modied groups could be connected in order to be secondarily functionalized through the binding part. 43,44 As shown in Fig. 1, the carboxyl group with charge compensation in L-DBTarA was used to substitute the aqua/hydroxo pair of the PCN-128Y metal cluster node to achieve the purpose of modication.…”
Section: Preparation and Characterization Of Chiral Modied Pcn-128ymentioning
confidence: 99%
“…1, the carboxyl group with charge compensation in L-DBTarA was used to substitute the aqua/hydroxo pair of the PCN-128Y metal cluster node to achieve the purpose of modication. 39,43,44 The chiral recognition sites were successfully introduced into the uorescence MOFs for the enantiodiscrimination of amino acids.…”
Section: Preparation and Characterization Of Chiral Modied Pcn-128ymentioning
confidence: 99%